2014
DOI: 10.22495/cocv12i1c9p12
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between audit committee characteristics, external auditors and economic value added (EVA) of public listed firms in Malaysia

Abstract: Malaysia is a developing economy which is one of the corporate leaders in South East Asian countries. Practicing audit committee is mandatory for public listed firms in Malaysia according to Bursa Malaysia Listing Requirements as well Malaysian Code of Corporate Governance. The purpose of this paper is to examine the association between audit committee characteristics and firm performance among public listed firms in Malaysia. This study employed EVA as performance measurement tool. The sample is 75 firm year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 53 publications
5
32
1
1
Order By: Relevance
“…Moreover, a routine of audit committee meeting can reduce the agency problem and information asymmetry as the audit committee can provide a fair and timely financial information to the management, shareholders and potential investors (Al-Mamun, Yasser, Rahman, Wickramasinghe, & Nathan, 2014;DeZoort, Hermanson, Archambeault, & Reed, 2002;Mallin, 2007). Furthermore, Xie et al (2003) found that the most frequent number of audit committee meeting, the lower the discretionary accruals, and hence it indicates better quality of financial reporting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, a routine of audit committee meeting can reduce the agency problem and information asymmetry as the audit committee can provide a fair and timely financial information to the management, shareholders and potential investors (Al-Mamun, Yasser, Rahman, Wickramasinghe, & Nathan, 2014;DeZoort, Hermanson, Archambeault, & Reed, 2002;Mallin, 2007). Furthermore, Xie et al (2003) found that the most frequent number of audit committee meeting, the lower the discretionary accruals, and hence it indicates better quality of financial reporting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So price changes that occur in high-end market does not have significant effect on purchase intention. Different opinion came from Mamun et. al.…”
Section: Relation Inter-variable Price Sensitivity Toward Purchase Inmentioning
confidence: 98%
“…A large board can significantly minimise the possibility of managerial opportunistic behaviour (Latif et al, 2016) and led to better decision-making and higher managerial monitoring (Ntim, 2015). Meanwhile, audit committee also fulfils a crucial role in deterring major financial risks and regarded as a significant component of the board with its responsibilities being largely fundamental for reliable and transparent financial information (Bhasin, 2016) by reducing information asymmetry (Al-Mamun et al, 2014). Therefore, audit committee will pressure the companies for a better whistleblowing system (Davidson et al, 2005) and leads to better whistleblowing disclosure (Lee & Fargher, 2012).…”
Section: The Role Of Board Of Directors In Encouraging Policiesmentioning
confidence: 99%